STUDY OF THE INFLUENCE OF AIRPORT VISIBILITY LIGHT SIGNAL COMPLEX FOR ACCURACY AIRCRAFT LANDING - Kazak , V. M.; Kravchuk , M. P.; Neklesa , A. O.; Chelnik , A. V.; Shcherbinin , A. A. (Problems of Informatization and Management, 2005)
The influence of aerodynamic light signal complex survivability on aircraft landing accuracy is considered, as well as the method of linear programming is used to find the optimal conditions for its landing at a given point of the runway.